Cesarean section in the perinatal center of iii level - indications and risk factors - Grishchenko, Olga; Korovay, Svitlana; Mamedova, Sevindzh Shahin Kizi (ScienceRise: Medical Science, 2020)
In the structure of labour, the frequency of caesarean section should not exceed 15%. Therefore, it is extremely important to clearly define clinical situations in which caesarean section can be abandoned and, conversely, identify pregnant women in whom it is advisable to plan a caesarean section to prevent urgent situations. The aim of the study was to study the structure of indications for emergency abdominal delivery in a level III medical department - the urban perinatal center of Kharkov to optimize childbirth tactics. Material and methods. Clinical and statistical analysis of pregnancy and childbirth histories of 550 women in labour who gave birth in the Kharkov city perinatal center during 2018-2019 was performed. The structure of the indications and the caesarean section frequency was analysed depending on clinical and anamnestic data using descriptive statistics methods, χ2 criterion and calculation of the odds ratio (OR) using the PSSР statistical software package. Results. The highest OR values were in diabetes mellitus, burdened gynecological history and cardiovascular diseases (OR more than 5.0). Gestational hypertension, first labour, genital tract infections, nervous system diseases, preeclampsia, obesity of the digestive system diseases, large fetus and vegetative-vascular dystonia (OR from 2.108 to 4.113) had a lesser effect, myopia, first pregnancy, and late reproductive age (OR from 1.619 to 1.958). Conclusion. The most common causes of emergency caesarean section were weak labour (29.5%) and fetal distress (13.2%). In 20.9% of women - concomitant diseases of the mother and large fetus. Indications for emergency caesarean section most often occurred in women in labour with diabetes mellitus, weighed down by a gynecological history and with cardiovascular diseases